A German climbing study on depression: A bouldering psychotherapeutic group intervention in outpatients compared with state-of-the-art cognitive behavioural group therapy and physical activation-study protocol for a multicentre randomised controlled trial - Dorscht, Lisa; Karg, Nina; Book, Stephanie; Grässel, Elmar; Kornhuber, Johannes; Luttenberger, Katharina (BMC Psychiatry, 2019)
Background: Besides classical approaches for treating depression, physical activity has been demonstrated to be an effective option. Bouldering psychotherapy (BPT) combines psychotherapeutic interventions with action-oriented elements from the field of climbing. The aim of this study is to investigate the effectiveness of BPT compared with a home-based exercise program (EP- A ctive control group, superiority trial) and state-of-the-art cognitive behavioural therapy (CBT-non-inferiority trial). Methods: The study is being conducted as a multicentre randomised controlled intervention trial at three locations in Germany. Participants are being randomised into three groups: BPT, CBT, or EP, each with a 10-week treatment phase. A power analysis indicated that about 240 people should initially be included. The primary outcome of the study is the Montgomery and Asberg Depression Rating Scale (MADRS) directly after the intervention. Additional measurement points are located three, six, and 12 months after the end of the intervention. The data are being collected via computer-assisted telephone interviews. Statistical analyses comprise regression analyses to test for the superiority of BPT over EP. To test for the non-inferiority of BPT and CBT, a non-inferiority margin of 1.9 points in the Patient Health Questionnaire (PHQ-9) and two non-inferiority margins for the MADRS (half of the two smallest Cohen's d values from the current meta-analyses) was predefined. The mean difference between CBT and EP is being used as a supplementary equivalence margin. Discussion: This is the first study to investigate the effect of a bouldering psychotherapy (BPT) on outpatients' depressive symptoms compared with mere physical activity (superiority analysis) and state-of-the-art cognitive behavioural therapy (CBT, non-inferiority analysis). Methodological strengths of the study are the elaborated, multicentred, randomised, controlled design. Assessors are blinded with regard to group allocation which leads to high objectivity. The study is conducted in a naturalistic setting, which leads to high external validity. Methodological limitations might be the clinical heterogeneity of the sample, which may dilute the intervention effects.
CRIS-Team Scopus Importer:2019-05-28
Keywords: Bouldering; Depression; Exercise program; Physical activity; Psychotherapy; Rock climbing; Sports

Bouldering psychotherapy is effective in enhancing perceived self-efficacy in people with depression: results from a multicenter randomized controlled trial - Kratzer, André; Luttenberger, Katharina; Karg-Hefner, Nina; Weiss, Maren; Dorscht, Lisa (BMC Psychology, 2021)
Background: Recent studies have suggested that therapeutic climbing/bouldering may have positive effects on perceived self-efficacy. Nevertheless, there is still an urgent need for high-quality studies, as many existing studies have suffered from methodological problems. Therefore, the current work was aimed at investigating the effect of a manualized bouldering psychotherapy (BPT) on perceived self-efficacy in people with depression, compared with a home-based physical exercise program (EP) and state-of-the-art cognitive behavioral group therapy (CBT). Methods: In a prospective, multicenter, randomized controlled trial, 233 people with depression were randomly assigned to one group (BPT, EP, or CBT). Perceived self-efficacy was assessed at baseline (t0) and directly after the 10-week intervention period (t1) with the GSE. In addition, depression was assessed with the PHQ-9 and the MADRS. We computed t tests, analyses of variance (ANOVAs), confounder-adjusted hierarchical regression analyses, mediation analyses, and several sensitivity analyses. Results: BPT participants showed a significantly larger increase in perceived self-efficacy on the GSE compared with the EP (an increase of 3.04 vs. 1.26 points, p =.016, Cohen’s d = 0.39). In the confounder-adjusted hierarchical multiple regression analysis, group allocation (BPT vs. EP) was found to be the only significant predictor of the postintervention GSE score (β =.16, p =.014) besides the baseline GSE score (β =.69, p <.001). No differences were found between BPT and CBT participants regarding the effect on perceived self-efficacy. Only in the CBT group, the relationship between depression at baseline and postintervention was partially mediated (23%) by perceived self-efficacy. Conclusions: Participation in the manualized BPT in a group setting leads to a clinically relevant enhancement of perceived self-efficacy in people with depression. This effect is superior to that of physical exercise alone. The results provide also initial indications that BPT is comparable to CBT in enhancing perceived self-efficacy, suggesting a strong case for a broader use of BPT as a supplement to existing health services. Future studies should focus on the modes of action of BPT and its effect on perceived self-efficacy in people with other mental or physical disorders. Trial registration ISRCTN12457760, registered partly retrospectively, 26 July 2017.
Created from Fastlane, Scopus look-up
Keywords: Bouldering; Depression; Physical Exercise; Psychotherapy; Self Efficacy; Therapeutic climbing

Bouldering psychotherapy is more effective in the treatment of depression than physical exercise alone: Results of a multicentre randomised controlled intervention study - Karg, Nina; Dorscht, Lisa; Kornhuber, Johannes; Luttenberger, Katharina (BMC Psychiatry, 2020)
Background: Recent scientific studies have suggested that climbing/bouldering is effective in alleviating depression when the comparison group was a waitlist control group, even when physical activity and other therapeutic approaches were controlled for. In the present study, we aimed to investigate the effectiveness of a manualised psychotherapeutic bouldering intervention for depressed individuals, compared with an active control group performing physical exercise alone. Methods: In a multicentre randomised controlled intervention trial, 133 outpatients with depression were assigned to either a bouldering psychotherapy (BPT) group or a home-based supervised exercise programme (EP). Severity of depression as the primary outcome was assessed at baseline and directly after a ten-week intervention period using the Montgomery-Åsberg Depression Rating Scale (MADRS). Secondary outcomes included anxiety, coping skills, self-esteem, body image, and interpersonal sensitivity. We applied t-tests to test for differences within the groups (t0 vs. t1) and between the BPT and the EP and a multiple regression analysis with the post-intervention MADRS score as the dependent variable. The robustness of estimates was investigated with a sensitivity analyses. Results: Patients in the BPT group showed a significantly larger decrease in depression scores compared with the EP on the MADRS (drop of 8.4 vs. 3.0 points, p =.002, Cohen's d = 0.55). In the confounder-adjusted regression analyses, group allocation was found to be the only significant predictor of the post-intervention MADRS score ( =-5.60, p =.001) besides the baseline MADRS score. Further significant differences in change scores between the BPT and the EP were found for anxiety (p =.046, d = 0.35), body image (p =.018, d = 0.42), and global self-esteem (p =.011, d = 0.45). Conclusions: The study provides evidence that the manualised BPT is not only effective in alleviating depressive symptoms but even goes beyond the effect of mere physical exercise. Based on these findings, the BPT should be considered as a complementary therapeutic approach. Trial registration: Trial identification number: ISRCTN12457760: Study KuS (Klettern und Stimmung-Climbing and Mood) combined boulder and psychotherapy against depression, registered retrospectively on July 26th, 2017.
CRIS-Team Scopus Importer:2020-03-27
Keywords: Bouldering; Depression; Physical exercise; Psychotherapy

Bouldering psychotherapy is not inferior to cognitive behavioural therapy in the group treatment of depression: A randomized controlled trial - Luttenberger, Katharina; Berking, Matthias; Kind, Leona; Weiss, Maren; Kornhuber, Johannes; Dorscht, Lisa; Karg-Hefner, Nina (British Journal of Clinical Psychology, 2021)
Objectives: Bouldering has shown promising results in the treatment of various health problems. In previous research, bouldering psychotherapy (BPT) was shown to be superior to a waitlist control group and to physical exercise with regard to reducing symptoms of depression. The primary aim of this study was to compare group BPT with group cognitive behavioural psychotherapy (CBT) to test the hypothesis that BPT would be equally as effective as CBT. Design: We conducted a randomized, controlled, assessor-blinded non-inferiority trial in which 156 outpatients meeting the criteria of a depressive episode according to the Diagnostic and Statistical Manual of Mental Disorders (DSM-IV) were randomly assigned to one of the two intervention groups (CBT: N = 77, BPT: N = 79). Methods: Intervention groups were manualized and treated for 10 weeks with a maximum of 11 participants and two therapists. The primary outcome was depressive symptom severity assessed with the Montgomery–Åsberg Depression Rating Scale (MADRS) and the Patient Health questionnaire (PHQ-9) at the beginning and end of the treatment phase as well as one year after the end of treatment. Result: In both groups, depressive symptoms improved significantly by an average of one severity level, moving from moderate to mild depressive symptoms after therapy (MADRS difference scores: BPT −8.06, 95% CI [−10.85, −5.27], p <.001; CBT −5.99, 95% CI [−8.55, −3.44], p <.001). The non-inferiority of BPT in comparison with CBT was established on the basis of the lower bound of the 95% confidence interval falling above all of the predefined margins. BPT was found to be effective in both the short (d = 0.89) and long term (d = 1.15). Conclusion: Group BPT was found to be equally as effective as group CBT. Positive effects were maintained until at least 12 months after the end of therapy. Thus, BPT is a promising approach for broadening the therapeutic field of therapies for depression. Practitioner points: Physical activity is effective in the treatment of depression and current guidelines explicitly recommend it as a complementary method for the treatment of depression. Nevertheless, body-related interventions are still underrepresented in current treatments for depression. Bouldering psychotherapy (BPT) combines physical activity with psychotherapeutic content. Its concept relies on proven effective factors from CBT such as exposure training, problem solving and practicing new functional behaviours and is thus an enrichment and implementation of CBT methods on the bouldering wall. The positive effect of group bouldering psychotherapy (BPT) in reducing depressive symptoms in outpatients with depression is not inferior to the effect of group cognitive behavioural therapy (CBT). Additionally the 10-weeks BPT-programme significantly improved symptoms of anxiety and interpersonal sensitivity as well as health-related quality of life, coping, body image, self-efficacy, and global self-esteem.
Created from Fastlane, Scopus look-up
Keywords: bouldering; cognitive behavioural therapy; depression; exercise; Group; physical activity; psychotherapy; rock climbing; sports

Dementia as a predictor of care-related quality of life in informal caregivers: a cross-sectional study to investigate differences in health-related outcomes between dementia and non-dementia caregivers - Karg, Nina; Grässel, Elmar; Randzio, Ottilie; Pendergrass, Anna (BMC Geriatrics, 2018)
BACKGROUND: The objectives of this study with a large sample of informal caregivers (CG) were a) to compare health-related outcomes of CGs caring for a patient with dementia and those caring for a relative with another chronic disease and b) to check whether dementia is a predictor of CG's care-related quality of life (QoL) in CarerQoL-7D. METHODS: This cross-sectional study involved self-reported data from 386 informal CGs who applied for an initial grade or upgrade of the care level of the care recipient at the Medical Service of Compulsory Health Insurance Funds of Bavaria (Germany). By obtaining data this way, systematic biases often associated with the acquisition of CGs were prevented. Bivariate and multiple analyses were conducted using a univariate covariance model (ANCOVA). RESULTS: Bivariate analyses showed significantly higher levels of subjective burden and lower QoL in the dementia group. No significant differences were found in terms of physical health and depressiveness, though there was a tendency suggesting higher levels of depressiveness in dementia CGs. Multiple analysis explaining QoL by dementia status after controlling for CG's sex, age and employment status revealed a significant effect of dementia, suggesting caregiving for a dementia patient was associated with lower QoL. CONCLUSIONS: Results of the study suggest that caring for a relative with dementia is associated with poorer health, i.e. greater levels of subjective burden and depressiveness, and predicts lower QoL in CGs. These findings emphasize the importance of specific interventions aiming to support informal CGs of dementia patients.
EVALuna2:211608

Predictors of the personal benefits and positive aspects of informal caregiving - Pendergrass, Anna; Mittelman, Mary; Grässel, Elmar; Özbe, Dominik; Karg, Nina (Aging & Mental Health, 2019)
Objective: We investigated a) the number of reported benefits in an informal caregiving situation and b) the factors that predict the caregiver's (CG's) experience of benefits. Method: In this cross-sectional study, we computed univariate analyses and a multiple regression analysis using a benefit score as the dependent variable. Participants were 734 informal CGs who provide care for a person with chronic care needs in Germany. We examined the CG's self-reported physical complaints (GBB-24), subjective burden (CSI), depressive symptoms (PHQ-9), quality of life (CarerQoL), and benefits (BIZA-D). Results: Most of the CGs (87.1%) experienced benefits in at least one field. A higher experience of benefits was significantly associated with: more depressive symptoms (r = 0.10), higher burden (r = 0.17), longer duration of care (r = 0.07), longer daily care time (r = 0.21), more physical complaints (r = 0.15), and a good quality of the relationship between CG and CR (eta = 0.13). In the multivariate regression analysis, a good relationship between the CG and CR (beta = .157, P < .001), an increased amount of care time (beta = .188, P < .001), and a higher level of burden (beta = .167, P < .001) were associated with greater CG's benefits. Conclusion: CG benefits are a very important, often experienced, but less-explored construct in caregiving research. Benefits do not seem to be on the opposite end of the same continuum as negative aspects of caregiving. Benefits appear to be a nearly distinct dimension in informal care settings.
CRIS-Team WoS Importer:2019-10-04